The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1186/s13014-014-0286-3
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Acuros (AXB) and Anisotropic Analytical Algorithm (AAA) for dose calculation in treatment of oesophageal cancer: effects on modelling tumour control probability

Abstract: AimTo investigate systematic changes in dose arising when treatment plans optimised using the Anisotropic Analytical Algorithm (AAA) are recalculated using Acuros XB (AXB) in patients treated with definitive chemoradiotherapy (dCRT) for locally advanced oesophageal cancers.BackgroundWe have compared treatment plans created using AAA with those recalculated using AXB. Although the Anisotropic Analytical Algorithm (AAA) is currently more widely used in clinical routine, Acuros XB (AXB) has been shown to more acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 28 publications
(34 reference statements)
0
23
0
Order By: Relevance
“…Since our fractionation scheme and studied algorithms were much different from these published works, direct comparison cannot be meaningfully made between our findings and their results. The radiobiological indices impact of AAA and ABX dose computation algorithms were published by Rana et al [ 45 ] and Padmanaban et al [ 46 ]. The study of Rana et al concluded that both AAA and AXB predicted comparable NTCP and TCP values for low-risk prostate cancer plans.…”
Section: Methodsmentioning
confidence: 99%
“…Since our fractionation scheme and studied algorithms were much different from these published works, direct comparison cannot be meaningfully made between our findings and their results. The radiobiological indices impact of AAA and ABX dose computation algorithms were published by Rana et al [ 45 ] and Padmanaban et al [ 46 ]. The study of Rana et al concluded that both AAA and AXB predicted comparable NTCP and TCP values for low-risk prostate cancer plans.…”
Section: Methodsmentioning
confidence: 99%
“…For whole breast cancer treatments, Petillion et al [14] show how the more advanced algorithms predicted a significantly lower TCP and NTCP for moderate breast fibrosis; the differences varied between 1 and 2.1% for TCP and between 2.9 and 5.5% for NTCP. In the study of Padmanaban et al [15] compared to the AAA algorithm, the AXB was found to significantly alter the tumor control probability (TCP) for treatment of oesophageal cancer.…”
Section: Introductionmentioning
confidence: 99%
“…[17] In our study that investigated the effects of the AAA algorithm and AXB algorithm on critical organ doses in breast radiotherapy, the findings showed that AAA calculated 2%, 2%, 8%, and 4% more dose for the left lung, heart, contralateral breast, and contralateral lung, respectively. [18] In a study conducted by Padmanaban et al, [19] AAA and AXB algorithms were compared using 3D conformal, and VMAT techniques in the treatment of esophageal cancer and the AXB algorithm was found to determine a low dose in PTV (0.5-1.3 Gy) compared to AAA. They showed that the low dose in PTV obtained for AXB was not related to the technique used.…”
Section: Discussionmentioning
confidence: 99%